Oolemma Receptors in Mammalian Molecular Fertilization: Function and New Methods of Study - Jiménez-Movilla, María; Hamze, Julieta G.; Romar, Raquel (Frontiers in Cell and Developmental Biology, 2021)
Fertilization is a key process in biology to the extent that a new individual will be born from the fusion of two cells, one of which leaves the organism in which it was produced to exert its function within a different organism. The structure and function of gametes is well known. However, we have a limited knowledge about the specific molecules participating in each of the steps of the fertilization process due to the transient nature of gamete interaction. Moreover, if we specifically focus in the fusion of both gametes’ membrane, we might say our molecular knowledge is practically null, despite molecular mechanisms of cell-to-cell adhesion are well studied in somatic cells. Moreover, between both gametes, the molecular knowledge in egg is even scarcer than in the spermatozoon for different reasons addressed in this review. Sperm-specific protein IZUMO1 and its oocyte partner, JUNO, are the first cell surface receptor pair essential for sperm-egg plasma membrane binding and fusion. Recently, thanks to gene editing tools and the development and validation of in vitro models, new oocyte molecules are being suggested in gamete fusion such as phosphatidylserine recognition receptors. Undoubtedly, we are in a new era for widening our comprehension on molecular fertilization. In this work, we comprehensively address the proposed molecules involved in gamete fusion, from the oocyte perspective, and the new study methods that are providing a better understanding of the role of new candidates in gamete fusion.